A critical review of the relationship between type 1 diabetes mellitus, inhibition, and behavioral management - Robertson, Neville Dean; Deacon, Elmari; Botha, Karel (Frontiers in Clinical Diabetes and Healthcare, 2023)
Type 1 diabetes mellitus is a chronic and lifelong condition that requires adequate behavior management in order to meet desired health outcomes. Type 1 diabetes mellitus affects the neurocognitive functioning of an individual. Inhibition is a core component within executive functioning and may play a vital role in the behavior management of type 1 diabetes mellitus. The aim of this study is to identify current gaps within existing knowledge regarding type 1 diabetes mellitus, inhibition, and behaviour management. This study employed a critical review design in order to analyse and synthesise current scientific literature. Twelve studies were identified through an appraisal process, and these were thematically analysed and integrated. The findings of this study indicate that a possible cycle arises between these three constructs, in which type 1 diabetes mellitus affects inhibition, inhibition affects behaviour management and poor behaviour management affects inhibition. It is recommended that future research should focus more specifically on this relationship.